2014
DOI: 10.1111/josh.12188
|View full text |Cite
|
Sign up to set email alerts
|

School‐Level Factors Associated With Increased Fruit and Vegetable Consumption Among Students in California Middle and High Schools

Abstract: This study suggests that institutional factors in schools are positively associated with middle and high school students' consumption of produce items at school. Additional efforts to structure school meal environments to enhance students' consumption of produce items can benefit students' nutrition and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 33 publications
2
30
1
Order By: Relevance
“…Surprisingly, among students consuming fruit, those from non-SB schools reported a higher amount of fruit consumption at lunch than students at schools with SBs, and there was no difference between the schools in vegetable consumption among those consuming vegetables. It is possible these unexpected findings may have resulted from a lack of environmental factors known to influence student use of SBs [29,30,31,32,33], such as a variety of quality produce, and attractive displays and signage [29,30]; therefore, a more in-depth study is required to determine the influence of these kinds of factors on student choice and consumption. It has previously been reported that increased variety of F/V leads to increased consumption [30], and inclusion of an examination of foods stocked in the SB would provide greater understanding of differences in consumption and would have implications for best practices relative to SB use [31].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, among students consuming fruit, those from non-SB schools reported a higher amount of fruit consumption at lunch than students at schools with SBs, and there was no difference between the schools in vegetable consumption among those consuming vegetables. It is possible these unexpected findings may have resulted from a lack of environmental factors known to influence student use of SBs [29,30,31,32,33], such as a variety of quality produce, and attractive displays and signage [29,30]; therefore, a more in-depth study is required to determine the influence of these kinds of factors on student choice and consumption. It has previously been reported that increased variety of F/V leads to increased consumption [30], and inclusion of an examination of foods stocked in the SB would provide greater understanding of differences in consumption and would have implications for best practices relative to SB use [31].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study found that longer lunch periods were associated with increased odds of consuming a fruit or vegetable, but the amounts consumed were not assessed. 9 …”
mentioning
confidence: 99%
“…Most salad bar studies focus on the elementary schools; this study included all grade levels participating in the NSLP. The literature on the benefits of salad bars to student F/V consumption is sparse with just a few studies reporting on student use of salad bars; only 2 studies suggest that salad bars themselves results in higher consumption of F/Vs . This study adds to the limited literature on school salad bars and suggests that school level resources (ie, placement location and/or perceived visibility) are related to school salad bars.…”
Section: Discussionmentioning
confidence: 76%